2012
DOI: 10.1038/onc.2012.126
|View full text |Cite
|
Sign up to set email alerts
|

Fas signaling promotes motility and metastasis through epithelial–mesenchymal transition in gastrointestinal cancer

Abstract: Fas signaling was reported to participate in cell apoptosis. However, this pathway has also been shown to promote tumor cell motility, leading to the hypothesis that Fas signaling may induce epithelial-mesenchymal transition (EMT) to promote metastasis. The effects of Fas-ligand (FasL) treatment and inhibition of Fas signaling on colorectal and gastric cancer cells were tested using motility assay, immunofluorescence, RT-PCR and immunoblot analyses. Fas signaling downregulated epithelial markers, upregulated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 29 publications
5
58
0
Order By: Relevance
“…18 The expression of CD95 on cancer cells suggests that cancer cells maintain CD95 expression for activities other than apoptosis induction. Consistent with this assumption are data demonstrating roles for CD95 in promoting cancer cell migration, growth, epithelial-to-mesenchymal transition (EMT), and development, as shown in lung cancer, 19,20 colon cancer, [21][22][23][24] gastrointestinal cancers, 25,26 pancreatic cancer, 27,28 glioblastoma multiforme (GBM), 29 and in 22 cell lines representing various cancers. 30 Our most recent finding is that cancer fails to develop in mouse models of low-grade or endometrioid ovarian cancer or liver cancer unless CD95 is expressed, 14,31 suggesting that the reason cancer cells usually express CD95 goes beyond a function of CD95 as a tumor promoter.…”
Section: Nonapoptotic Signaling Through Cd95 In Normal Cells and In Csupporting
confidence: 49%
“…18 The expression of CD95 on cancer cells suggests that cancer cells maintain CD95 expression for activities other than apoptosis induction. Consistent with this assumption are data demonstrating roles for CD95 in promoting cancer cell migration, growth, epithelial-to-mesenchymal transition (EMT), and development, as shown in lung cancer, 19,20 colon cancer, [21][22][23][24] gastrointestinal cancers, 25,26 pancreatic cancer, 27,28 glioblastoma multiforme (GBM), 29 and in 22 cell lines representing various cancers. 30 Our most recent finding is that cancer fails to develop in mouse models of low-grade or endometrioid ovarian cancer or liver cancer unless CD95 is expressed, 14,31 suggesting that the reason cancer cells usually express CD95 goes beyond a function of CD95 as a tumor promoter.…”
Section: Nonapoptotic Signaling Through Cd95 In Normal Cells and In Csupporting
confidence: 49%
“…Although the mechanisms of migration are still poorly understood, EMT and mesenchymal-epithelial transition is a good model to explain how solid tumors metastasize from the site of origin to a new site. [29][30][31] Herein, we showed that GPR120 signaling promoted migration and induced EMT of CRC cells in vitro and in xenograph mouse model. Furthermore, we found that expression of GPR120 and E-cadherin was inversely correlated in CRC specimens, suggesting that GPR120 might induce EMT in vivo.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 88%
“…Expression of CD95L ( Supplementary Fig. S3) seems to be associated with impaired prognosis in other malignancies as well (30). The main reason for a poor outcome in glioblastoma is therapy resistance, the highly invasive behavior as well as the local immunosuppression.…”
Section: Discussionmentioning
confidence: 99%